The Effects of Reduced Annulus in Roof Bolting Performance - Stephen Tadolini (International Conference on Ground Control in Mining, 1998)
The annulus thickness, for bolts anchored with resin, effects the systems final performance. Recent developments in the manufacturing process of these support systems, coupled with improved resin characteristics, have resulted in design changes to minimize hole drilling requirements and reduce resin usage. The amount of resin to properly anchor a 7/8-SRD (Special Rolled Dimensions) bolt in a 25.4 mm (1-in) diameter hole has been reduced to about one-third of the resin required to anchor a No. 7 rebar bolt (22 mm (7/8-in) diameter) traditionally installed in a 35 mm (1-3/8-in) diameter borehole. More importantly, laboratory and field tests, indicate that higher bond strengths and anchorage capacities can be realized with reduced annulus systems. These factors have a direct bearing on reinforcement efficiency and subsequent roof support performance.